2008
DOI: 10.1111/j.1365-2567.2008.02820.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor‐4‐mediated macrophage activation is differentially regulated by progesterone via the glucocorticoid and progesterone receptors

Abstract: Summary Macrophage function has been demonstrated to be subject to modulation by progesterone. However, as this steroid hormone can act through the glucocorticoid receptor as well as the progesterone receptor, the mechanism of action has not been precisely characterized. To determine the mode of action, we compared the ability of progesterone, norgestrel (a synthetic progesterone‐receptor‐specific agonist) and dexamethasone (a synthetic glucocorticoid receptor agonist) to modulate macrophage function following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 72 publications
2
80
0
1
Order By: Relevance
“…In contrast, a further study reported that progesterone treatment of resting murine splenic DCs resulted in increased expression of MHC class II and CD40 and enhanced T cell stimulatory activity (25). Progesterone is a ligand for the glucocorticoid receptor (GR) as well as the progesterone receptor (PR), and we have already demonstrated that progesterone can differentially regulate macrophage cytokine production by using individual receptors (26). In the current study, we therefore determined, using bone marrow-derived DCs (BMDCs), whether DC TLR-induced cytokine production and maturation was also GR or PR dependent.…”
mentioning
confidence: 99%
“…In contrast, a further study reported that progesterone treatment of resting murine splenic DCs resulted in increased expression of MHC class II and CD40 and enhanced T cell stimulatory activity (25). Progesterone is a ligand for the glucocorticoid receptor (GR) as well as the progesterone receptor (PR), and we have already demonstrated that progesterone can differentially regulate macrophage cytokine production by using individual receptors (26). In the current study, we therefore determined, using bone marrow-derived DCs (BMDCs), whether DC TLR-induced cytokine production and maturation was also GR or PR dependent.…”
mentioning
confidence: 99%
“…Although we did not observe any direct effects of physiological doses of progesterone and estradiol on macrophage polarization ( Fig. 14 and paper I, supplemental Table I), these and other hormones may modulate the effects of inflammatory stimuli on decidual macrophages. In support of this notion, treatment with progesterone or the glucocorticoid receptor agonist dexamethasone reduced the production of nitric oxide, IL-12 and TNF from mouse macrophages in response to LPS (Miller and Hunt, 1998;Jones et al, 2008).…”
Section: Consistent With An M2 Phenotype Cd14mentioning
confidence: 91%
“…Progesterone has been shown to suppress the development of Th1 cells while promoting Th2 cells and the production of IL-10 (Miyaura and Iwata, 2002) and to induce production of M-CSF and leukemia inhibitory factor (LIF), shown to be essential for murine pregnancy (Piccinni et al, 2001). Progesterone has also been suggested to modulate the activation of macrophages (Jones et al, 2008;Menzies et al, 2011). The effects of estradiol have been proposed to be concentration-dependent, with low concentrations promoting IFN-γ production and Th1 immunity and high levels stimulating IL-10 secretion and Th2 immunity (Whitacre et al, 1999;Beagley and Gockel, 2003).…”
Section: Immune Regulation During Pregnancymentioning
confidence: 99%
“…Costa et al [742] showed that T. gondii infection slightly upregulated glucocorticoid-induced TNF receptor expression in Treg cells and B cells, but the most robust increment in expression was observed in macrophages and dendritic cells] These findings are consistent with the results obtained by Nishikawa et al [743] that T. gondii decreased NO production in the peritoneal macrophages, and with the suggestion that the parasite could partially decrease NO production in the infected host cells and therefore escape the immune defense reaction in the host [744] . Jones et al [745] also found that DXM (the GC receptor ligand) significantly reduced LPS-induced macrophages production of NO. It was reported that DXM can inhibit iNOS expression in LPS-treated murine macrophages by destabilizing the mRNA transcript [746] .…”
Section: T Gondii Infectionmentioning
confidence: 95%